2019
DOI: 10.1186/s12896-019-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous hydrolysis with lipase and fermentation of rapeseed cake for iturin A production by Bacillus amyloliquefaciens CX-20

Abstract: BackgroundRapeseed cake (RSC), as the intermediate by-product of oil extraction from the seeds of Brassica napus, can be converted into rapeseed meal (RSM) by solvent extraction to remove oil. However, compared with RSM, RSC has been rarely used as a raw material for microbial fermentation, although both RSC and RSM are mainly composed of proteins, carbohydrates and minerals. In this study, we investigated the feasibility of using untreated low-cost RSC as nitrogen source to produce the valuable cyclic lipopep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Figure 3D showed that the cell viability dropped proportionally with the increase of ethanolic extract, whatsoever its origin and at 8 g/L where the production iturin A by B amyloliquefaciens CX-20 was completely stopped, there was less than 0.05% of viable bacterial cells. This result indicated that the inhibition of iturin A production was most probably due to the loss of viability of the cell caused by the toxicity of the ethanolic extracts, which was consistent with the previous report ( Chen et al, 2019b ). Phenolic compounds are found in plants as defense mechanisms and always have antimicrobial activity.…”
Section: Resultssupporting
confidence: 93%
“…Figure 3D showed that the cell viability dropped proportionally with the increase of ethanolic extract, whatsoever its origin and at 8 g/L where the production iturin A by B amyloliquefaciens CX-20 was completely stopped, there was less than 0.05% of viable bacterial cells. This result indicated that the inhibition of iturin A production was most probably due to the loss of viability of the cell caused by the toxicity of the ethanolic extracts, which was consistent with the previous report ( Chen et al, 2019b ). Phenolic compounds are found in plants as defense mechanisms and always have antimicrobial activity.…”
Section: Resultssupporting
confidence: 93%
“…Iturin A was extracted according to reported method (Chen et al ., 2019b). Briefly, 0.3 ml of the mixed fermentation broth was pipetted into a 3 ml glass tube containing 1.2 ml of methanol, shaken well and then leached for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…A in different reports [34][35][36][37][38][39] The domestic and international research status of Iturin A over the past 15 years is displayed in Table 1. Iturin A is produced predominantly by the Bacillus strain using soybean meal powder, yeast extract powder, glucose, and maize starch as the principal carbon and nitrogen sources.…”
Section: Fermentation Production Of Iturinmentioning
confidence: 99%